2005
DOI: 10.1542/peds.2005-0784
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Clinical Presentation of Neonatal Hemochromatosis in Twins

Abstract: ABSTRACT. Neonatal hemochromatosis (NH) is a rare disease of gestation that results in fetal liver injury and extrahepatic siderosis. The etiology of NH is not fully understood. However, the rate of recurrence of NH in the pregnancy after an affected one is ϳ80%. A spectrum of liver disease has been recognized, spanning from liver failure in the fetus or neonate to infants that survive with medical therapy. Here we report on 2 sets of fraternal twins, each set with a gross disparity in the severity of presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…Affected twins may have different clinical presentations; with one twin severely affected and the other minimally so. 41 Interestingly, infants with NH often have persistent patency of the ductus venosus on ultrasound. 2,42 This finding is of unclear clinical significance.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Affected twins may have different clinical presentations; with one twin severely affected and the other minimally so. 41 Interestingly, infants with NH often have persistent patency of the ductus venosus on ultrasound. 2,42 This finding is of unclear clinical significance.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…We have shown that twins may have disparate clinical findings, with one severely affected and the other minimally so. 25 It is one of the most commonly recognized causes of liver failure in the neonate. 26 The presenting findings are those of acute liver failure and usually multiorgan failure.…”
Section: Neonatal Hemochromatosismentioning
confidence: 99%
“…Survival rates with this treatment have been generally reported as low. 4,6,15,16,19,20,24,29 In the patients studied by Murray and Kowdley 4 and Sigurdsson et al, 24 chelation-antioxidant therapy was not efficacious. Rodrigues et al 20 concluded in their study that this therapy did not appear to modify the outcome in NH, at least in severe cases, and recommended liver transplantation as the treatment of choice.…”
Section: Discussionmentioning
confidence: 93%